1988
DOI: 10.1128/iai.56.8.2180-2188.1988
|View full text |Cite
|
Sign up to set email alerts
|

CS31A, a new K88-related fimbrial antigen on bovine enterotoxigenic and septicemic Escherichia coli strains

Abstract: The nature of the common surface antigen of six hemagglutinating and adhesive piliated Escherichia coli strains isolated from diarrheic or septicemic calves was studied. By electron microscopy studies, the E. coli surface antigen designated CS31A was found on bacterial cells and in purified form to consist of thin (2-nm) "fibrillar" fimbriae. E. coli 31A, which was cured of a 105-megadalton plasmid, failed to express CS31A fimbriae, but retained the ability to hemagglutinate and to adhere in vitro on intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 39 publications
10
80
0
2
Order By: Relevance
“…After centrifugation at 12 000 x g for 10 min, the resulting supernatant was used for experiments. CS31A fibrillae-specific rabbit antiserum (anti-CS3lA) was obtained as described by Girardeau et al (1988). mAb 3b.5 (Delmas et al, 1990) and mAb 1AF10 (Gebauer et al, 1991) raised, respectively, against the C and A sites of TGEV-S on native coronavirus, were used.…”
Section: Characterization Of the Expressed Cipg::tgev Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…After centrifugation at 12 000 x g for 10 min, the resulting supernatant was used for experiments. CS31A fibrillae-specific rabbit antiserum (anti-CS3lA) was obtained as described by Girardeau et al (1988). mAb 3b.5 (Delmas et al, 1990) and mAb 1AF10 (Gebauer et al, 1991) raised, respectively, against the C and A sites of TGEV-S on native coronavirus, were used.…”
Section: Characterization Of the Expressed Cipg::tgev Hybridsmentioning
confidence: 99%
“…3 legend by using as primary Ab either (a) anti-ClpG pAb, or (b) 3b.5 mAb, or (c) 1AF10 mAb, or (d) anti-G15Q pAb, or (e) anti-T15P pAb. ClpG subunit-specific rabbit antiserum (anti-ClpG pAb) was obtained as described by Girardeau et al (1988). The G15Q peptide (GQLQAVNPNAGNRGQ) and the T15P peptide (TFTNPVVSTTQWSAP) correspond to the aa residues 185-199 and 235-249 of CIpG, respectively.…”
Section: Characterization Of the Expressed Cipg::tgev Hybridsmentioning
confidence: 99%
“…Studies in recent years revealed that F17 fimbrial adhesins are somewhat heterogeneous and they form a so-called F17 family of fimbriae (F17a, F17b, F17c, F17d and G fimbriae) based on their receptor specificities (Le Bougouénec and Bertin, 1999). Another (non-fimbrial) surface protein (CS31A) has also been associated with calf diarrhoea (Girardeau et al, 1988) but it is also detected on septicaemic E. coli from calves, in contrast to K99 or F41. Interestingly, CS31A is genetically related to K88 fimbria (known as a typical porcine adhesin) (Girardeau et al, 1988).…”
Section: Adhesins and Receptors For Etec Of Calvesmentioning
confidence: 99%
“…Another (non-fimbrial) surface protein (CS31A) has also been associated with calf diarrhoea (Girardeau et al, 1988) but it is also detected on septicaemic E. coli from calves, in contrast to K99 or F41. Interestingly, CS31A is genetically related to K88 fimbria (known as a typical porcine adhesin) (Girardeau et al, 1988). In fact, the N-terminal sequence of purified CS31A shows a homologous protein of 26.77 kDa between CS31A, F41 and K88, indicating an evolutionary relationship between these fimbrial and afimbrial adhesions (Girardeau et al, 1991).…”
Section: Adhesins and Receptors For Etec Of Calvesmentioning
confidence: 99%
“…The HB101 E. coli strain was used as a negative control. The P4271 E. coli strain was the reference strain producing K88 ¢brillae [13]. The 47 CS31A-positive strains and the 28 CS31A-negative strains used to validate the PCR detection of the clpG gene were from our own collection.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%